Development of Video-Based Learning Model Through “Seesaw” Application to Improve Process Skills Reviewed from the Motivation and Initial Understanding of Vocational High School Students - Prahestiningtyas, Tatag; Sulisworo, Dwi (Journal of Vocational Education Studies, 2025)
Knowing how much learning has improved in students after using Physics learning media based on Video-Based Learning through the “Seesaw” application. This study employed a One-Group Pre-test Post-test Design. 34 SMK Bhakti Mulia Blora 10th-grade students served as the study's samples. The Simple Random Sampling technique was used to sample the sample members. Pre-experiment tests and questionnaires provided the data, which were then analyzed using paired t-tests. By using the "Seesaw" program to create instructional films, teachers can cut down on the amount of time they spend teaching and standardize the way that lesson materials are delivered. Additionally, because they are able to take in and comprehend the instructional information more thoroughly, kids become more engaged in the learning process, which makes learning more exciting overall. Teachers may easily plan and construct learning activities, assessments, and records of student work by using the "Seesaw" program. Students performed better in the post-test than they did in the pre-test. Additionally, student performance has improved from cycle to cycle. When utilizing the "Seesaw" program for video-based learning in Physics, students' process abilities have improved as opposed to manual learning.